The Children's Ciranda and the landless children: education and life in movement - Santos Barcellos, Luis Henrique dos [UNESP]; Torres, Julio Cesar [UNESP] (Univ Nove Julho, 2019)
This article has as research object the Child Education of the Movement of Landless Rural Workers (MST - abbreviation in Brazilian Portuguese). The MST is the main Brazilian movement for struggle and resistance for land and land reform. In order to defend its ideals, the Movement chooses, as one of the main factors, the development of an emancipatory education, that should join work and education, managed through democratic relations. Using a methodology research of bibliographical nature and documentary analysis, we investigated the educational proposal of MST for childhood in the context of the Children's Ciranda, trying to comprehend the concepts of children and childhood Without Land. The MST seeks to highlight social inequality, neglect, and negligence with the real needs of the peasant population. The child in this process is inserted as participatory subject, since birth, in the struggles against capital. In addition to being subject of rights, it is a subject of struggle.
Keywords: Countryside Education; MST; Children's Ciranda